Pequeno encontro com a morte: masoquismo, psicanálise, literatura - Julia de Sena Machado (2011)
The present work starts from the approximation made by Freud, in distinct moments of his work, among passivity, feminine, and death, in what concerns the enigma of masochism. We begin our work with a revision of the texts in which Freud grants privilege to such enigma, selecting two ways in which he approaches the issue: one based on biology and another one based on individual history. Afterwards, we attempt to rescue the sources of the term masochism in order to verify if this triad (passivity feminine death) is also present in the literary work of Sacher-Masoch. Based on a particular conception of literature, we highlight Gilles Deleuzes critiques to the Freudian interpretation of masochism, as well as the philosophers assertion concerningthe existence of a contractual role in masochism. Finally, based on the psychoanalytic method and on Jean Laplanches Theory of the Generalized Seduction, we present an interpretation of the most renowned work of Masoch, Venus in Furs (1870). We verifyhow the three elements highlighted by Freud upon approaching masochism are present in this work, and how the literary narrative may contribute to the clinical discussions concerning masochism, bringing up, once again, the enigma.